2011
DOI: 10.1007/s11408-011-0155-0
|View full text |Cite
|
Sign up to set email alerts
|

Competition in securities markets: the impact on liquidity

Abstract: Competition for order flow is widely documented for U.S. markets, but is a relatively new phenomenon in European equities trading. Only with the Markets in Financial Instruments Directive, which went into effect in November 2007, did new trading venues emerge in Europe that for the first time ever seriously threatened established exchanges. Chi-X, one of the new competitors, has gained a considerable market share, eroding the traditional exchanges' share of equities trading volumes. As the proliferation of new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…They conclude that, due to the presence of a single consolidated tape, sophisticated order routing technologies and prohibition of trade-throughs, equity markets in the USA are virtually consolidated into a single market with multiple points of entry. Other empirical studies like Hengelbrock and Theissen (2009), Chlistalla and Lutat (2011), and Gomber et al (2011a also observe a positive impact of competition between similarly organized limit order markets on liquidity. In addition, Boehmer and Boehmer (2003) document a similarly positive impact on liquidity of increased competition in the ETF market after the NYSE started trading ETFs primarily traded on the AMEX.…”
Section: Welfare Analysis Of Market Fragmentation and Competitionmentioning
confidence: 81%
“…They conclude that, due to the presence of a single consolidated tape, sophisticated order routing technologies and prohibition of trade-throughs, equity markets in the USA are virtually consolidated into a single market with multiple points of entry. Other empirical studies like Hengelbrock and Theissen (2009), Chlistalla and Lutat (2011), and Gomber et al (2011a also observe a positive impact of competition between similarly organized limit order markets on liquidity. In addition, Boehmer and Boehmer (2003) document a similarly positive impact on liquidity of increased competition in the ETF market after the NYSE started trading ETFs primarily traded on the AMEX.…”
Section: Welfare Analysis Of Market Fragmentation and Competitionmentioning
confidence: 81%
“…• Many of these articles find positive associations between fragmentation and liquidity (Branch and Freed (1977), Hamilton (1979), Neal (1987), Cohen and Conroy (1990), Battalio (1997), Mayhew (2002), Weston (2002), Boehmer and Boehmer (2003), De Fontnouvelle and Harris 2003, Fink et al (2006), Nguyen, Van Ness, andVan Ness (2007), Foucault and Menkveld (2008), Chlistalla and Lutat (2011), O'Hara and Ye (2011), and Menkveld (2013)). Particularly relevant to our article are the articles by He et al (2015) and Aitken et al (2017), who also study the Australian market, finding liquidity to improve on average in conjunction with the 2011 entry of Chi-X.…”
Section: B Empiricsmentioning
confidence: 99%
“…For example, Hendershott and Mendelson (2000) and Hendershott and Jones (2005) found that there was a reduction in price efficiency after Island ECN stopped displaying its limit order book. Chlistalla and Lutat (2011) finds that the entrance of Chi-X, a dark pool in the US, decreased spread.…”
Section: A Summary Of Testable Empirical Predictionsmentioning
confidence: 99%